The Effect Of Information Quality And Trust In Purchasing Decisions On The Lazada Marketplace (Case Study in Students of the Faculty of Economics and Business Muhammadiyah University of Bengkulu) - Adek Nurhalimah; Taufik Bustami (Penerbit Jurnal Indonesia, 2023)
The title of this research is the effect of Information Quality and Trust on Purchasing Decisions on the Lazada Marketplace. This research aims to determine the effect of Information Quality and Trust in Purchasing Decisions on the Lazada Marketplace. The study was conducted in December 2021 – February 2022. This research sample is a Lazada Marketplace consumer at the Faculty of Economics and Business Students at the Muhammadiyah University of Bengkulu with the number is 150 people. The sampling technique is probability sampling. The method used in this study is a quantitative method with multiple linear regression analysis using SPSS 24 for windows. Based on the results of multiple linear regression obtained the following equation form: Y = 6,350 – 0.679 (X1) – 0.288 (X2). The results of the study and hypotheses in this study show that the Quality of Information (X1) and Trust (X2) have a positive and significant effect both partially and simultaneously on purchasing decisions (Y) on the Lazada Marketplace in the Muhammadiyah University of Bengkulu environment..